Lysurus fossatii (Lysuraceae, Basidiomycota) - Hernández Caffot, María Luciana (2022)
Lysurus fossatii, a new Lysuraceae species with unique macroscopic features is described andillustrated. Specimens were collected during field expeditions to remnants of the Espinal forestpreserved at Estancia Yucat, South-East Córdoba, in central Argentina. The species is diagnosedby a light yellow peridium when immature, with the surface marked by a reticulum correspondingto the peridial sutures. When young and while still enclosed in the peridium, this species can bedistinguished by the presence of a small white stipe completely covered by a green gleba. No actualreceptacular structure is evidenced and only the stipe supports the gleba. Phylogenetic analyseshighly supported the affinity of this species with L. sphaerocephalus in a close clade of L. cruciatus.